Synthesis of manganese dioxide/iron oxide/graphene oxide magnetic nanocomposites for hexavalent chromium removal1. Issue 67 (24th July 2015) - Liu, Yan; Luo, Chao; Cui, Guijia; Yan, Shiqiang
<x xml:space="preserve">Abstract</x> Effective removal of heavy metal ions from wastewater is one of the important environment issues.